2005
DOI: 10.1074/jbc.m501480200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis of Synthetic Human Serum Albumin α-Helix 28 Identifies Structural Distortion upon Amadori Modification

Abstract: The non-enzymatic reaction between reducing sugars and long-lived proteins in vivo results in the formation of glycation and advanced glycation end products, which alter the properties of proteins including charge, helicity, and their tendency to aggregate. Such protein modifications are linked with various pathologies associated with the general aging process such as Alzheimer disease and the long-term complications of diabetes. Although it has been suggested that glycation and advanced glycation end products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
3
26
1
Order By: Relevance
“…Further, K 97 is part of a di-lysine motif and it is generally accepted that these are more susceptible to glycation due to local acid-base catalysis making one residue more nucelophilic. 36 The fact that K 97 was least reactive in the freeze-dried samples investigated here suggests that the local structural environment, accessibility, and charge of the lysine residues is different to that found in solution and crystal forms. Further studies to elucidate such differences between the solution and glassy state are therefore required and we note that previous studies in solution using peptide models have shown that the local environment does influence the rate of glycation and local secondary structure elements on glycation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Further, K 97 is part of a di-lysine motif and it is generally accepted that these are more susceptible to glycation due to local acid-base catalysis making one residue more nucelophilic. 36 The fact that K 97 was least reactive in the freeze-dried samples investigated here suggests that the local structural environment, accessibility, and charge of the lysine residues is different to that found in solution and crystal forms. Further studies to elucidate such differences between the solution and glassy state are therefore required and we note that previous studies in solution using peptide models have shown that the local environment does influence the rate of glycation and local secondary structure elements on glycation.…”
Section: Discussionmentioning
confidence: 74%
“…Also, the linking of formulation to activity is not common. 5,11,36 There was an obvious change in lytic activity only in those lysozyme samples formulated in pH 6.2 buffer and heated for 24 h at 90 C (Table 2). However, here we have shown that while changes in activity are not always measurable (Table 2), there may be chemical modification to the protein (Table 3) occurring that could potentially lead to changes in the antigenicity of the protein.…”
Section: Discussionmentioning
confidence: 98%
“…1a) is an often used model protein to study the pyranose ring-opening reaction of glucose and protein glycation by many techniques, notably mass spectrometry, to obtain information about glycation site (16,18,29,30). To understand the mechanism and the structural determinant for glycation, we determined the crystal structure of rHSA in complex with glucose.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of such modifications on protein structure has been far less investigated. Recently, using nuclear magnetic resonance (NMR), Howard et al [28] have showed that glycation of a model helical peptide from human serum albumin (HSA) by glucose caused distortion of the helical structure of the protein at the point of glycation. Another protein structural study for the changes induced by non-enzymatic glycation in the secondary and tertiary protein structure of HSA showed that the in general protein structure was unaltered.…”
Section: Synthesismentioning
confidence: 99%